Determination of Phosphatidylcholine in Artificial Crude Soybean Oil by Biosensor Based on Horseradish Peroxidase/Choline Oxidase-Modified Glassy Carbon Electrode - WANG Donghua, WANG Xu, WANG Yuting, GAO Shan, WANG Weining, YANG Fuming, YU Dianyu (Shipin Kexue)
A biosensor for the determination of phosphatidylcholine (PC) in artificial crude soybean oil was fabricated by immobilizing horseradish peroxidase (HRP) and choline oxidase (ChOx) onto on a glassy carbon electrode (GCE) modified with multi-walled carbon nanotube (MWCNTs), SnO2 and chitosan (CS). Under the conditions of ChOx and HRP addition each at 2.5 U and pH 7.5, the sensor showed significant electrochemical response to PC. PC concentrations in the range of 10–300 mg/L were linearly correlated with the peak current, and the detection limit was 2 mg/L. Recoveries for spiked samples ranged from 90% to 110% with relative standard deviations (RSDs) less than 4.68%. Good correlation was observed between the results of the biosensor and those of high performance liquid chromatography (HPLC) with a correlation coefficient (r) of 0.992 9. After 14 days of storage, the sensor still retained 98% of its initial current value, indicating its good stability. This study can provide theoretical support for the rapid inspection and control of vegetable oil refining.